THE EFFECT OF WORK COMMUNICATION, TEAMWORK, AND WORK DISCIPLINE ON PERSONNEL PERFORMANCE AT THE LUBUK BAJA POLICE SECTION, BARELANG POLICE - Anggara, Risky; Sumardin, Sumardin; Mulyadi, Mulyadi; Sabri, Sabri (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of work communication, teamwork, and work discipline on the performance of personnel at the Lubuk Baja Police Station, Barelang City Police Station. The approach used is quantitative with a survey method. Respondents in this study amounted to 46 personnel who were all sampled through saturated sampling techniques. The data collection instrument was a questionnaire, while the data analysis technique used SPSS version 19 software. Hypothesis testing was carried out through simple regression analysis and multiple regression, t-test, and F-test. The results showed that work communication had a significant effect on personnel performance with a calculated t value of 10.470 greater than the t table of 1.664. Teamwork also had a significant effect on personnel performance with a calculated t value of 14.483 greater than the t table of 1.664. Furthermore, work discipline was proven to have a significant effect on personnel performance with a calculated t value of 15.757 greater than the t table of 1.664. Simultaneously, work communication, teamwork, and work discipline have a significant effect on personnel performance, as indicated by the calculated F value of 39.798, which is greater than the F table of 2.49. This finding confirms that improving personnel performance can be achieved through strengthening communication, solid teamwork, and consistent work discipline.